Short-range micro-motion sensing with radar technology - Gu, Changzhan; Lien, Jaime (Institution of Engineering and Technology, 2019)
Covering radar sensor hardware, digital signal processing and machine learning, the book provides researchers and practitioners with insights into the latest advancements in the field.
Keywords: Radar.; Motion detectors.; elektronické knihy; electronic books